A new isolation and evaluation method for marine-derived yeast spp with potential applications in industrial biotechnology - Zaky, Abdelrahman Saleh; Greetham, Darren; Louis, Edward J.; Tucker, Gregory A.; Du, Chenyu (Korean Society for Microbiology and Biotechnology, 2016)
Yeasts that are present in marine environments have evolved to survive hostile environments that are characterized by high exogenous salt content, high concentrations of inhibitory compounds, and low soluble carbon and nitrogen levels. Therefore, yeasts isolated from marine environments could have interesting characteristics for industrial applications. However, the application of marine yeast in research or industry is currently very limited owing to the lack of a suitable isolation method. Current methods for isolation suffer from fungal interference and/or low number of yeast isolates. In this paper, an efficient and nonlaborious isolation method has been developed and successfully isolated large numbers of yeasts without bacterial or fungal growth. The new method includes a three-cycle enrichment step followed by an isolation step and a confirmation step. Using this method, 116 marine yeast strains were isolated from 14 marine samples collected in the UK, Egypt, and the USA. These strains were further evaluated for the utilization of fermentable sugars (glucose, xylose, mannitol, and galactose) using a phenotypic microarray assay. Seventeen strains with higher sugar utilization capacity than the reference terrestrial yeast Saccharomyces cerevisiae NCYC 2592 were selected for identification by sequencing of the ITS and D1/D2 domains. These strains belonged to six species: S. cerevisiae, Candida tropicalis, Candida viswanathii, Wickerhamomyces anomalus, Candida glabrata, and Pichia kudriavzevii. The ability of these strains for improved sugar utilization using seawater-based media was confirmed and, therefore, they could potentially be utilized in fermentations using marine biomass in seawater media, particularly for the production of bioethanol and other biochemical products.